Defect engineering in two-dimensional perovskite nanowire arrays by europium(iii) doping towards high-performance photodetection. Issue 56 (24th June 2022) - Guan, Yuwei; Liang, Jie; Zhao, Yiman; Liu, Zhen; Zhou, Zhonghao; Ji, Shiyang; Jia, Yajun; Hu, Fengqin; Zhao, Yong Sheng
Abstract : We demonstrate high-performance photodetectors based on Eu-doped 2D perovskite nanowire arrays. Thanks to the efficient carrier transport and suppressed trap density, the optimized Eu-doped photodetectors show an excellent responsivity of 6.24 A W −1 . Abstract : We demonstrate high-performance photodetectors based on Eu-doped 2D perovskite nanowire arrays. The pure crystallographic orientation enables efficient carrier transport and the doped Eu ions effectively suppress the trap density in the nanowire arrays. As a result, the optimized Eu-doped photodetectors show an excellent responsivity of 6.24 A W −1, an outstanding specific detectivity of 5.83 × 10 13 Jones and stable photo-switching behavior with a current on/off ratio of 10 3 .